Metal biosorption by surface-layer proteins from Bacillus species - Allievi, Mariana Caludia (2011)
Bacillus species have been involved in metal association as biosorbents, but there is not a clear understanding of this chelating property. In order to evaluate this metal chelating capacity, cultures and spores from Grampositive bacteria of species either able or unable to produce surface layer proteins (S-layers) were analyzed for their capacity of copper biosorption. Only those endowed of S-layers, like Bacillus sphaericus and B. thuringiensis, showed a significant biosorption capacity. This capacity (nearly 50%) was retained after heating of cultures, thus supporting that structural elements of the envelopes are responsible for such activity. Purified Slayers from two Bacillus sphaericus strains had the ability to biosorb copper. Copper biosorption parameters were determined for strain B. sphaericus 2362, and after analyses by means of the Langmuir model, the affinity and capacity were shown to be comparable to other bacterial biosorbents. A competitive effect of Ca2+ and Zn2+, but not of Cd2+, was also observed, thus indicating that other cations may be biosorbed by this protein. Spores that have been shown to be proficient for copper biosorption were further analyzed for the presence of Slayer content. The retention of S-layers by these spores was clearly observed, and after extensive treatment to eliminate the S-layers, the biosorption capacity of these spores was significantly reduced. For the first time, a direct correlation between S-layer protein content and metal biosorption capacity is shown. This capacity is linked to the retention of S-layer proteins attached to Bacillus spores and cells.